Pembrolizumab alone or combined with chemotherapy versus chemotherapy as first-line therapy for advanced urothelial carcinoma (KEYNOTE-361): a randomised, open-label, phase 3 trial. Issue 7 (July 2021) - Powles, Thomas; Csőszi, Tibor; Özgüroğlu, Mustafa; Matsubara, Nobuaki; Géczi, Lajos; Cheng, Susanna Y-S; Fradet, Yves; Oudard, Stephane; Vulsteke, Christof; Morales Barrera, Rafael; Fléchon, Aude; Gunduz, Seyda; et al.
Summary: Background: PD-1 and PD-L1 inhibitors are active in metastatic urothelial carcinoma, but positive randomised data supporting their use as a first-line treatment are lacking. In this study we assessed outcomes with first-line pembrolizumab alone or combined with chemotherapy versus chemotherapy for patients with previously untreated advanced urothelial carcinoma. Methods: KEYNOTE-361 is a randomised, open-label, phase 3 trial of patients aged at least 18 years, with untreated, locally advanced, unresectable, or metastatic urothelial carcinoma, with an Eastern Cooperative Oncology Group performance status of up to 2. Eligible patients were enrolled from 201 medical centres in 21 countries and randomly allocated (1:1:1) via an interactive voice-web response system to intravenous pembrolizumab 200 mg every 3 weeks for a maximum of 35 cycles plus intravenous chemotherapy (gemcitabine [1000 mg/m 2 ] on days 1 and 8 and investigator's choice of cisplatin [70 mg/m 2 ] or carboplatin [area under the curve 5] on day 1 of every 3-week cycle) for a maximum of six cycles, pembrolizumab alone, or chemotherapy alone, stratified by choice of platinum therapy and PD-L1 combined positive score (CPS). Neither patients nor investigators were masked to the treatment assignment or CPS. At protocol-specified final analysis, sequential hypothesis testing began with superiority of pembrolizumab plus chemotherapy versus chemotherapy alone in the total population (all patients randomly allocated to a treatment) for the dual primary endpoints of progression-free survival (p value boundary 0·0019), assessed by masked, independent central review, and overall survival (p value boundary 0·0142), followed by non-inferiority and superiority of overall survival for pembrolizumab versus chemotherapy in the patient population with CPS of at least 10 and in the total population (also a primary endpoint). Safety was assessed in the as-treated population (all patients who received at least one dose of study treatment). This study is completed and is no longer enrolling patients, and is registered at ClinicalTrials.gov, number NCT02853305 . Findings: Between Oct 19, 2016 and June 29, 2018, 1010 patients were enrolled and allocated to receive pembrolizumab plus chemotherapy (n=351), pembrolizumab monotherapy (n=307), or chemotherapy alone (n=352). Median follow-up was 31·7 months (IQR 27·7–36·0). Pembrolizumab plus chemotherapy versus chemotherapy did not significantly improve progression-free survival, with a median progression-free survival of 8·3 months (95% CI 7·5–8·5) in the pembrolizumab plus chemotherapy group versus 7·1 months (6·4–7·9) in the chemotherapy group (hazard ratio [HR] 0·78, 95% CI 0·65–0·93; p=0·0033), or overall survival, with a median overall survival of 17·0 months (14·5–19·5) in the pembrolizumab plus chemotherapy group versus 14·3 months (12·3–16·7) in the chemotherapy group (0·86, 0·72–1·02; p=0·0407). No further formal statistical hypothesis testing was done. In analyses of overall survival with pembrolizumab versus chemotherapy (now exploratory based on hierarchical statistical testing), overall survival was similar between these treatment groups, both in the total population (15·6 months [95% CI 12·1–17·9] with pembrolizumab vs 14·3 months [12·3–16·7] with chemotherapy; HR 0·92, 95% CI 0·77–1·11) and the population with CPS of at least 10 (16·1 months [13·6–19·9] with pembrolizumab vs 15·2 months [11·6–23·3] with chemotherapy; 1·01, 0·77–1·32). The most common grade 3 or 4 adverse event attributed to study treatment was anaemia with pembrolizumab plus chemotherapy (104 [30%] of 349 patients) or chemotherapy alone (112 [33%] of 342 patients), and diarrhoea, fatigue, and hyponatraemia (each affecting four [1%] of 302 patients) with pembrolizumab alone. Six (1%) of 1010 patients died due to an adverse event attributed to study treatment; two patients in each treatment group. One each occurred due to cardiac arrest and device-related sepsis in the pembrolizumab plus chemotherapy group, one each due to cardiac failure and malignant neoplasm progression in the pembrolizumab group, and one each due to myocardial infarction and ischaemic colitis in the chemotherapy group. Interpretation: The addition of pembrolizumab to first-line platinum-based chemotherapy did not significantly improve efficacy and should not be widely adopted for treatment of advanced urothelial carcinoma. Funding: Merck Sharp and Dohme, a subsidiary of Merck, Kenilworth, NJ, USA.